Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1167/iovs.13-12527
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Control Using Toric Orthokeratology (TO-SEE Study)

Abstract: Toric ortho-k lenses can slow axial elongation effectively in myopic children with moderate-to-high astigmatism. (ClinicalTrials.gov number, NCT00978692.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
198
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(221 citation statements)
references
References 53 publications
12
198
1
3
Order By: Relevance
“…The cause of this apparent shortening of axial length remains unclear. No other studies have reported prolonged shortening of axial length over the course of treatment, although a shortening of axial length has commonly been observed at the initiation of ortho-k lens wear, attributed at least in part to central corneal thinning 9,11,12,17,18 and choroidal thickening. [31][32][33] Central corneal thinning reflects the redistribution of corneal tissue and this change usually stabilizes within a few weeks, once the optimal refractive correction has been achieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cause of this apparent shortening of axial length remains unclear. No other studies have reported prolonged shortening of axial length over the course of treatment, although a shortening of axial length has commonly been observed at the initiation of ortho-k lens wear, attributed at least in part to central corneal thinning 9,11,12,17,18 and choroidal thickening. [31][32][33] Central corneal thinning reflects the redistribution of corneal tissue and this change usually stabilizes within a few weeks, once the optimal refractive correction has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Data from two studies, ROMIO 11 and TO-SEE, 17 were pooled for analysis. Both studies were approved by the Departmental Research Committee of the School of Optometry of The Hong Kong Polytechnic University and written consent was obtained from both subjects and their parents before study participation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16e23 All of these studies utilized the conventional clinical study protocol of comparing 1 group of subjects wearing OK lenses with a separate matched control group of subjects wearing spectacles 16,18e23 or conventional soft contact lenses. 17 Only recently have the results from truly randomized clinical trials been reported 20,22,23 dmost early studies either used historical controls 16,17 or allowed subject self-selection into study or control groups. Typically, these previous studies have been conducted over a 2-year period of lens wear, although an article reporting 5 years of OK lens wear has been recently published.…”
Section: Discussionmentioning
confidence: 99%